An Overview of Antennal Esterases in Lepidoptera - Godoy, Ricardo; Machuca, Juan; Venthur, Herbert; Quiroz, Andrés; Mutis, Ana (Frontiers in Physiology, 2021)
Lepidoptera are used as a model for the study of insect olfactory proteins. Among them, odorant degrading enzymes (ODEs), that degrade odorant molecules to maintain the sensitivity of antennae, have received less attention. In particular, antennal esterases (AEs) (responsible for ester degradation) are crucial for intraspecific communication in Lepidoptera. Currently, transcriptomic and genomic studies have provided AEs in several species. However, efforts in gene annotation, classification, and functional assignment are still lacking. Therefore, we propose to combine evidence at evolutionary, structural and functional level to update ODEs as well as key information into an easier classification, particularly of AEs. Finally, the kinetic parameters for putative inhibition of ODEs is discussed in terms of its role in future integrated pest management strategies.